2021
DOI: 10.21775/cimb.041.171
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Cytoplasm: Delivery of the Alphaherpesvirus Genome to the Nucleus

Abstract: Herpesviruses virions are large and complex structures that deliver their genetic content to nuclei upon entering cells. This property is not unusual as many other viruses including the adenoviruses, orthomyxoviruses, papillomaviruses, polyomaviruses, and retroviruses, do likewise. However, the means by which viruses in the alphaherpesvirinae subfamily accomplish this fundamental stage of the infectious cycle is tied to their defining ability to efficiently invade the nervous system. Fusion of the viral envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 227 publications
0
5
0
Order By: Relevance
“…GBP1 remodels the host actin cytoskeleton, whereas HSV-1 hijacks the host cytoskeleton for capsid trafficking. 27 , 28 , 29 Therefore, we hypothesize that GBP1 disturbs actin cytoskeleton to hinder HSV-1 capsid trafficking. To test this hypothesis, we first treated HSV-1-infected cells with a widely used actin cytoskeleton polymerization inhibitor, cytochalasin D (CytoD), and found that CytoD treatment effectively disrupted cytoskeletal organization ( Figure 5 A) and impeded the nuclear translocation of the HSV-1 genome as expected ( Figures 5 B and 5C).…”
Section: Resultsmentioning
confidence: 97%
“…GBP1 remodels the host actin cytoskeleton, whereas HSV-1 hijacks the host cytoskeleton for capsid trafficking. 27 , 28 , 29 Therefore, we hypothesize that GBP1 disturbs actin cytoskeleton to hinder HSV-1 capsid trafficking. To test this hypothesis, we first treated HSV-1-infected cells with a widely used actin cytoskeleton polymerization inhibitor, cytochalasin D (CytoD), and found that CytoD treatment effectively disrupted cytoskeletal organization ( Figure 5 A) and impeded the nuclear translocation of the HSV-1 genome as expected ( Figures 5 B and 5C).…”
Section: Resultsmentioning
confidence: 97%
“…As mentioned above, during HSV-1 reactivation from latency in TG neurons at high MOI ( 17 19 ), tens of HSV-1 virus capsids simultaneously adsorb to NPCs on a single cell nucleus and eject viral genomes ( 10 , 11 ). [This process is repeated as empty capsids detach and new DNA-loaded capsids are docked at the NPCs in vivo ( 35 ).] A single round of HSV-1 DNA ejections leads to internalization of millions of base pairs of viral DNAs in the nucleus; HSV-1 DNA quickly decondenses once in the nucleus, occupying three times more volume than in the capsid ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, a PPI network centering on HSV tegument proteins was also generated ( Fig. 2 ) [ 2 , 7 , [24] , [25] , [26] , [27] ]. Most PPIs have been detected in lysates (by immunoprecipitation) or cells (yeast two-hybrid or complementation assay of split marker), but not in the tegument.…”
Section: Ppi Network Of Ebv Tegument Proteins and With Nucleocapsid A...mentioning
confidence: 99%
“…The tegument of herpesviruses is mainly composed of viral proteins, with some cellular proteins. Tegument proteins do not comprise a solid structure like the nucleocapsid and, thus, a portion of the tegument structure can be released into the cytoplasm when the viral envelope fuses with the plasma membrane or endosomal membrane [ 2 ]. Some types of tegument proteins form interfaces with the exterior of the nucleocapsid (the inner tegument), and some others with membrane proteins on the interior surface of the envelope (outer tegument).…”
Section: Introductionmentioning
confidence: 99%